2007
DOI: 10.1145/1278387.1278392
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual environments to assess time-to-contact judgments from pedestrian viewpoints

Abstract: This paper describes the use of desktop and immersive virtual environments to study judgments that pedestrians make when deciding to cross a street. In particular, we assess the ability of people to discriminate and estimate time-to-contact (TTC) for approaching vehicles under a variety of conditions. Four experiments observing TTC judgments under various conditions are described. We examine the effect of type of vehicle, viewpoint, presentation mode, and TTC value on TTC judgments. We find no significant effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…We found that the accuracy of TTA judgments decreased with increasing TTA. These results agree with the laboratory based results of Schiff and Detwiler, 9 Schiff and Oldak, 7 and Seward et al 11 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that the accuracy of TTA judgments decreased with increasing TTA. These results agree with the laboratory based results of Schiff and Detwiler, 9 Schiff and Oldak, 7 and Seward et al 11 …”
Section: Discussionsupporting
confidence: 92%
“…Having subjects make instantaneous TTA decisions about approaching vehicles is however more realistic to the actual task of crossing the street than waiting to make the decision until the car reaches the judgment point. Interestingly, when Seward et al 11 used an immersive virtual environment, which may be considered to be more realistic to the real-world than films used in the laboratory based experiments, they found that subjects on average overestimated the TTA by 0.77 seconds, which was similar to our results. Thus it is possible that there is a tendency to have less overall error in making TTA judgments when assessing performance in a more realistic environment as opposed to testing performance using two-dimensional films.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For instance , Te Velde et al [2005] simulated traffic environments with artificial indoor streets, or Sidaway et al [1990] and Tung et al [2008] used prerecorded road environment videos in their experiments. However, VEs and virtual reality technology have emerged as the preferred tool to simulate interactive traffic environments (e.g., Simpson et al [2003]; Seward et al [2007]). Since safety-training can effectively improve pedestrian traffic safety [Barton et al 2007], but reasonable real-world environments for traffic safety training are expensive and difficult to realize, computer generated VEs also found great reception for safety-training simulators [Oxley et al 2008;Cavallo et al 2009;Schwebel and McClure 2010].…”
Section: Pedestrian Safetymentioning
confidence: 99%